Should be the School Inspection the innovation driver at educational establishments? - Alcalá Ibáñez, María Lourdes (Avances en Supervisión Educativa, 2016)
This presentation is intended to be a reflection on the role to be played by inspectors of education in the new social and educational scenario faced by schools and teachers of the 21st century. The traditional way of performing the functions of monitoring, evaluation and counseling does not allow inspectors to respond to the new needs of schools and the educational system. Its mission has to change; it has to break inertias and go beyond documentary supervision and the search for specific solutions to problems generated in (educational) centers. Inspectors should lead collaborative work with other external agents, who provide centers with the necessary support needed in the search for innovative educational projects involving the curricular and methodological transformation in the classroom.